Development and evaluation of a methodology for developing websites - Issa, Tomayess (Curtin University, 2007)
This research focuses on the development of a new methodology for creating effective websites, especially those used for marketing. It was found that existing methodologies were missing some key stages - user participation and “real interaction” (i.e. monitoring of user interaction with a prototype site). This has led to users being frustrated and lacking loyalty to the website. There is great potential for combining aspects of methodologies from different disciplines; however, these need to be integrated in a coherent way. To address these problems, a new integrated methodology was developed in this research. The new methodology was created from basic concepts derived from: lifecycle models; Information Systems development methodologies; methodologies with explicit human factors aspects; websites methodologies; marketing methodologies; and additional techniques such as task analysis and detailed website design and implementation. After studying the lifecycle model, the researcher identified four key principles, which were the foundation of the research: user participation; iteration; usability and “real interaction”. The way in which these four principles were incorporated in each methodology was evaluated in order to choose the strongest stages to utilize in the new combined methodology. After reviewing techniques for methodology integration, a new draft methodology was produced. To assess the new methodology, two research phases were used - interviews and a questionnaire. In the former phase, the researcher interviewed representatives from nine website development companies in Western Australia to discuss their current methodologies and compared these with the new methodology.Most of the industry participants were pleased with the structure of the new methodology, as most agreed that it incorporates the necessary requirements to develop a successful website. The interviews generated some recommendations for revisions to the methodology, which assisted the researcher to improve the new methodology. In the latter phase, an online questionnaire was completed by a total of website industry participant andInformation Systems Professionals, in order to assess the revised methodology. Results from the interviews and questionnaire supported the research hypothesis – i.e. that the new integrated methodology can provide a more effective way of developing websites, utilizing the four key principles. This thesis points to the need for further research, including the development of a website describing the new methodology. This website will incorporate a software tool to facilitate selection of particular stages, steps and techniques from theintegrated methodology to produce a tailored methodology for any specific project, thereby implementing the concept of “contingency”.